2004
DOI: 10.17221/3639-pse
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity comparison of some possible toxic metals (Cd, Cu, Pb, Se, Zn) on young seedlingsof Sinapis alba L.

Abstract: The chronic ecotoxicological effects of Cd, Cu, Pb, Se and Zn were determined within this study. Mustard seedlings (Sinapis alba L.) were used as a model subject for the tests. The phytotoxicity was determined through the root growth inhibition and photosynthetic pigments production (chlorophyll a, b, total carotenoids). The metal accumulation in the roots and cotyledons was also determined using the AAS methods. On the basis of IC 50 values and their 95% confidence intervals (CI) for the root elongation of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 22 publications
10
38
0
1
Order By: Relevance
“…However, further increase in Se concentrations reduced shoot biomass production. Our results are in agreement with Fargašová (2003) who observed an inhibitory effect of Se on the mustard growth. In general, the biomass production was higher when selenate was supplied to the nutrient solution than selenite ( Figure 1A).…”
Section: Plant Materials and Experimental Designsupporting
confidence: 94%
“…However, further increase in Se concentrations reduced shoot biomass production. Our results are in agreement with Fargašová (2003) who observed an inhibitory effect of Se on the mustard growth. In general, the biomass production was higher when selenate was supplied to the nutrient solution than selenite ( Figure 1A).…”
Section: Plant Materials and Experimental Designsupporting
confidence: 94%
“…Growth inhibition by the heavy metals (1mM concentration) was in the order: Cu > Cd > Zn > Pb (Table 1). These results were in agreement with those of Fargašová [3], who reported that trace elements had toxic inhibitory effects of on the mustard seedling in a descending order of Cu > Se > Cd > Zn > Pb. Unlike our experiment the later authors, included Se in their study.…”
Section: Characterization Of Nano-fe3o4supporting
confidence: 93%
“…At the highest Se level supplied (6 mg/kg) there was observed a reduction in shoot yield of 9 and 15%, when Se was supplied as selenite and selenate, respectively (7 and 14% for root yield). Our results are in agreement with Fargašová (2003) who observed an inhibitory effect of Se on the mustard growth. The diverse effect of selenate and selenite on the growth of brachiaria plants could be caused by distinct mechanisms of metabolism of different Se forms (Sors et al 2005).…”
Section: Resultssupporting
confidence: 94%